Budget Participation and Managerial Performance: Bridging the Gap through Budget Goal Clarity - Alhasnawi, Mushtaq; Said, Ridzwana Mohd; Daud, Zaidi Mat; Muhamad, Haslinah (Advances in Social Sciences Research Journal, 2023)
Budget participation is an important management tool that improves employee motivation, commitment, and performance by providing a sense of ownership and control over the budgeting process. This study examines the impact of budget participation on managerial performance in higher education institutions (HEIs). More specifically, the research aims to investigate the effect of budget participation on managerial performance through the mediating role of budget goal clarity. A survey was conducted with 373 low- to middle-level managers from HEIs in Iraq, and the research model was tested using PLS-SEM. The results indicate that budget participation positively influences budget goal clarity, which, in turn, positively affects managerial performance. Furthermore, the study reveals that budget goal clarity partially mediates this relationship. The strategic integration of these findings into managerial practices and decision-making processes can unleash substantial and tangible benefits in terms of employee engagement, skyrocketing productivity, and overall organizational success.